Engineering a Promiscuous Tautomerase into a More Efficient Aldolase for Self‐Condensations of Linear Aliphatic Aldehydes. (30th May 2017) - Rahimi, Mehran; van der Meer, Jan‐Ytzen; Geertsema, Edzard M.; Poelarends, Gerrit J.
Abstract: The enzyme 4‐oxalocrotonate tautomerase (4‐OT) from Pseudomonas putida mt‐2 takes part in a catabolic pathway for aromatic hydrocarbons, where it catalyzes the conversion of 2hydroxyhexa‐2, 4‐dienedioate into 2‐oxohexa‐3‐enedioate. This tautomerase can also promiscuously catalyze carbon–carbon bond‐forming reactions, including various types of aldol reactions, by using its amino‐terminal proline as a key catalytic residue. Here, we used systematic mutagenesis to identify two hotspots in 4‐OT (Met45 and Phe50) at which single mutations give marked improvements in aldolase activity for the self‐condensation of propanal. Activity screening of a focused library in which these two hotspots were varied led to the discovery of a 4‐OT variant (M45Y/F50V) with strongly enhanced aldolase activity in the self‐condensation of linear aliphatic aldehydes, such as acetaldehyde, propanal, and butanal, to yield α, β‐unsaturated aldehydes. With both propanal and benzaldehyde, this double mutant, unlike the previously constructed single mutant F50A, mainly catalyzes the self‐condensation of propanal rather than the cross‐condensation of propanal and benzaldehyde, thus indicating that it indeed has altered substrate specificity. This variant could serve as a template to create new biocatalysts that lack dehydration activity and possess further enhanced aldolase activity, thus enabling the efficient enzymatic self‐coupling of aliphatic aldehydes. Abstract : Engineering a promiscuous enzyme : We have used a systematic mutagenesis strategy, followed by combinatorial mutagenesis of identified "hotspot" positions and activity screening, to greatly enhance the aldolase activity of 4‐oxalocrotonate tautomerase for the self‐condensation of linear aliphatic aldehydes thus yielding α, β‐unsaturated aldehydes.